Deterrence of Online Child Sexual Abuse and Exploitation. (18th April 2018) - Quayle, Ethel; Koukopoulos, Nikolaos
Abstract: 'Cyberspace' has added a dimension to the ecology of the child and should be a starting point for practitioners (including police) to think about digital media in the context of child sexual abuse. While there is no evidence to suggest that online abuse and exploitation is a more serious offence than crimes occurring offline, the behaviours enabled by social media may present a significant risk factor for some children. This article gives a brief overview of the phenomena and prevalence of online child sexual abuse and exploitation and the role that the Internet may play. This is considered in relation to deterrence, prevention and management of these crimes, and further develops a public health approach to online child abuse and exploitation. Finally, the article critically considers emerging evidence to support this interaction between the individual and the online environment.